The lived experiences of a COVID-19 immunization programme: vaccine hesitancy and vaccine refusal - Chan, Nee Nee *; Ong, Khang Wei; Siau, Ching Sin; Lee, Kai Wei; Peh, Suat Cheng *; Shakila, Yacob; Chia, Yook Chin *; Seow, Vei Ken; Ooi, Pei Boon * (BMC (Springer Nature), 2022)
Background: The COVID-19 pandemic has resulted in a global health emergency and lock-down measures to curb the uncontrolled transmission chain. Vaccination is an effective measure against COVID-19 infections. In Malaysia amidst the national immunisation programme (NIP) which started in February 2021, there were rising concerns regarding the prevalence of vaccine hesitancy and refusal, and therefore, vaccine uptake among Malaysians. Although there are many quantitative studies on COVID-19 vaccination, the subjective experience of individuals was understudied. This study aims to explore the lived experiences of Malaysians regarding vaccine hesitancy and refusal, and facilitating factors that could enhance vaccine acceptance and uptake.